Effect of Arsenic on Breastfed Baby of Arsenic Affected Lactating Mother (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: In the endemic areas of chronic arsenic poisoning of Bangladesh (Cumilla, Noakhali, Laksham, Matlab) drinking water is heavily contaminated with arsenic. An estimated of about 70 million people are at risk from drinking water contaminated with arsenic. There are numerous data on effects of arsenic in adults but a few reports are available on the adverse effect of arsenic on infants and arsenic concentration in human milk, as human milk is the primary source of nutrition during first 6 months of life. Arsenic level found in the urine of infants reflects the intake of arsenic through breast milk.Objective: To find out the effect of arsenic among the breastfed babies of arsenic affected mothers.Materials and Methods: This cross sectional study was conducted in the arsenic exposed area of Bangladesh from January 2007 to July 2008. Thirty exclusively breastfed babies of arsenic affected mothers were enrolled as cases and 30 exclusively breastfed babies from non affected mothers were taken as control. Urinary arsenic concentration was considered for measurement of arsenic status. Mothers with their babies were thoroughly examined for length, weight, occipitofrontal circumference (OFC) and gross motor skills.Results: Arsenic affected mothers excreted high concentration of arsenic (334.68μgm/L±108.02) in their urine than control group (19.17μgm/L±7.92) but the urinary arsenic concentrations from both groups of breast fed babies were found to be low. Growth and development parameters like length, weight, OFC and gross motor skills were also found to be normal in both groups of babies.Conclusion: Exclusive breast feeding should be practiced in arsenic affected area to protect the babies from exposure to arsenic from water sources.Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 99-102